Health utilities for non‐melanoma skin cancers and pre‐cancerous lesions: A systematic review - C. So; A. E. Cust; L. G. Gordon; R. L. Morton; K. Canfell; P. Ngo; M. Dieng; K. McLoughlin; C. Watts (Wiley, 2021)
Abstract Background Non‐melanoma skin cancers (NMSCs) are common and consume many healthcare resources. A health utility is a single preference‐based value for assessing health‐related quality of life, which can be used in economic evaluations. There are scarce data on health utilities for NMSCs. Objectives Using a systematic review approach, we synthesized the current data on NMSC‐related health utilities. Methods A systematic review of studies of NMSC‐related health utilities was conducted in Medline, Embase, and Cochrane databases. Data were extracted based on the protocol and a quality assessment was performed for each study. Results The protocol resulted in 16 studies, involving 121 621 participants. Mean utility values across the studies ranged from 0.56 to 1 for undifferentiated NMSC, 0.84 to 1 for actinic keratosis, 0.45 to 1 for squamous cell carcinoma, and 0.67 to 1 for basal cell carcinoma. There was considerable variability in utilities by type of cancer, stage of diagnosis, time to treatment, treatment modality, and quality of life instrument or method. Utility values were predominantly based on the EuroQol 5‐dimension instrument and ranged from 0.45 to 0.96, while other measurement methods produced values ranging from 0.67 to 1. Lower utility values were observed for advanced cancers and for the time period during and immediately after treatment, after which values gradually returned to pre‐treatment levels. Conclusions Most utility values clustered around relatively high values of 0.8 to 1, suggesting small decrements in quality of life associated with most NMSCs and their precursors. Variability in utilities indicates that careful characterization is required for measures to be used in economic evaluations.